A physicochemical investigation of membrane fouling in cold microfiltration of skim milk - Tan, Teng Ju; Wang, Dan; Moraru, Carmen (Elsevier Science, 2014)
The main challenge in microfiltration (MF) is membrane fouling, which leads to a significant decline in permeate flux and a change in membrane selectivity over time. This work aims to elucidate the mechanisms of membrane fouling in cold MF of skim milk by identifying and quantifying the proteins and minerals involved in external and internal membrane fouling. Microfiltration was conducted using a 1.4-μm ceramic membrane, at a temperature of 6 ± 1°C, cross-flow velocity of 6 m/s, and transmembrane pressure of 159 kPa, for 90 min. Internal and external foulants were extracted from a ceramic membrane both after a brief contact between the membrane and skim milk, to evaluate instantaneous adsorption of foulants, and after MF. Four foulant streams were collected: weakly attached external foulants, weakly attached internal foulants, strongly attached external foulants, and strongly attached internal foulants. Liquid chromatography coupled with tandem mass spectrometry analysis showed that all major milk proteins were present in all foulant streams. Proteins did appear to be the major cause of membrane fouling. Proteomics analysis of the foulants indicated elevated levels of serum proteins as compared with milk in the foulant fractions collected from the adsorption study. Caseins were preferentially introduced into the fouling layer during MF, when transmembrane pressure was applied, as confirmed both by proteomics and mineral analyses. The knowledge generated in this study advances the understanding of fouling mechanisms in cold MF of skim milk and can be used to identify solutions for minimizing membrane fouling and increasing the efficiency of milk MF.